Engaged, but not actively involved: A narrative review and reflections on radiographers’ engagement in research within the clinical setting. - Andersen, Eivind Richter (Radiography Open, 2025)
Aim To contribute to the ongoing debate of radiography research, by providing an overview of radiographers’ engagement in research activities within the clinical setting. Barriers and facilitators for research engagement will be discussed. Methods An unstructured search for literature was conducted in MEDLINE, PUBMED and Google Scholar. Snowballing on references was further conducted. The search included papers written in English published between 2014 and august 2024. Results Radiographers are generally positive about research, however, their active participation in research activities in clinical settings is limited. The primary barriers to engagement in research are systemic, while facilitators are present at both personal (individual motivators) and systemic levels. Conclusion Enhancing radiography research is critical to ensure that radiographers work according to the principles of Evidence-based Practice, which is essential for patient safety and the provision of high-quality care. A research culture must be established within the local departments. Several strategic steps are proposed to develop a research strategy within the departments. Further research should focus on evaluating the implementation and outcomes of efforts to enhance research participation in clinical radiography.